2015
DOI: 10.1093/scan/nsv108
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain imaging predicts public health campaign success

Abstract: Mass media can powerfully affect health decision-making. Pre-testing through focus groups or surveys is a standard, though inconsistent, predictor of effectiveness. Converging evidence demonstrates that activity within brain systems associated with self-related processing can predict individual behavior in response to health messages. Preliminary evidence also suggests that neural activity in small groups can forecast population-level campaign outcomes. Less is known about the psychological processes that link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 44 publications
10
101
0
Order By: Relevance
“…Nielsen [40] further promotes qualitative user research for collecting insights to drive the design, not the number of involved people. In Case Study 1, we asked the participants to experiment with a commercial MAR application featuring an interactive cat (described in Section 4.1) and then administered a questionnaire based on [41] about emotions that the participants felt during the experiment. The questionnaire consisted of basic information, such as gender, age and previous experiences with MAR.…”
Section: Participantsmentioning
confidence: 99%
“…Nielsen [40] further promotes qualitative user research for collecting insights to drive the design, not the number of involved people. In Case Study 1, we asked the participants to experiment with a commercial MAR application featuring an interactive cat (described in Section 4.1) and then administered a questionnaire based on [41] about emotions that the participants felt during the experiment. The questionnaire consisted of basic information, such as gender, age and previous experiences with MAR.…”
Section: Participantsmentioning
confidence: 99%
“…In social marketing, apart from a few exceptions not concerning the environmental issues (e.g. Zelinková et al, 2014Mauri et al, 2014, Falk et al, 2015 such methods have not been commonly used so far for the purpose of evaluating the role of media messaging in social campaigns. What is more, no attempts to obtain valuable information on the basis of merging data from different sources (neuroscientific tools and questionnaires) have been made as well.…”
Section: Evaluation Of Media Message Effectivenessmentioning
confidence: 99%
“…It is also considered to be a part of the default network of the brain that is active during “rest”, which is thought to consist primarily of mind wandering and self-directed thought (Andrews-Hanna et al, 2014, 2010). Related to this, it is considered a key region associated with self-referential thought (Denny et al, 2012; Falk et al, 2015, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Specific to cigarette smoking, one study that found that vmPFC activity in response to GWLs predicted population-level engagement with an online smoking cessation presentation (Falk et al, 2015). Most recently, a 2016 study showed that neural activation in the vmPFC and amygdala during GWLs predicted CO verified changes in smoking behavior over a two week period (Riddle et al, 2016).…”
Section: Introductionmentioning
confidence: 99%